Linkage Analysis of Tourette Syndrome in a Large Utah Pedigree - Knight, Stacey (2010)
Tourette Syndrome (TS) is a neuropsychiatric disorder characterized by multiple motor and phonic tics. The heritability of TS has been well established, yet there is a lack of consensus in genome-wide linkage studies. The purpose of this study was to conduct a genome-wide linkage analysis on a unique, large, high-risk TS Utah pedigree. We examined a qualitative trait (TS1) where cases had a definitive diagnosis of TS as observed by a clinical interviewer (n=66) and a quantitative phenotype based on the total Yale global motor and phonic tic severity scores (n=102). Both parametric and non-parametric multipoint linkage analyses based on MCMC methods were performed using a 10cM spaced micro-satellite autosomal marker set. Two regions of interest were identified under affecteds-only recessive models; a LOD score of 3.3 on chromosome 1p for Yale tic severity and a LOD score of 3.1 on chromosome 3p for the TS1 phenotype. Twenty-seven individuals shared linked segregating haplotypes for the 1p region. They had significantly higher Yale tic phonic scores than non-sharers (p=0.01). There were 46 haplotype sharers on chromosome 3p with significantly higher percentage of females among these individuals compared to the non-sharers (p=0.03). The significant linkage peaks on chromosomes 1p and 3p are in new areas of the genome for TS, and replication of these findings is necessary.